On-line monitoring of electric power system for controlled islanding (2015)
Monitoring and controlling of large power systems is becoming more challenging as a consequence of the growth of their size, increasing demand for electricity, penetration of variable renewable energy sources, uncertainty in many operating parameters, and the growing number of interconnections. Therefore, system operators feel the need for a real-time wide area monitoring, protection and control system that provides more accurate information about the state of the power system and assists operators in the implementation of corrective actions to operate at high levels of security and reliability and to respond rapidly to disturbances. Synchronized measurement technology, which allow taking synchronized measurements from widely dispersed locations, has made possible the development of real-time wide area monitoring systems. At present, phasor measurements units (PMUs) are the devices most used for power system monitoring. When a PMU is placed at a bus, it can provide an accurate measurement of the voltage phasor (magnitude and angle), as well as the current phasors through the incident transmission lines.